Characteristics of suicide decedents with no federally funded mental health service contact in the 12 months before death in a population‐based sample of Australians 45 years of age and over. Issue 1 (10th November 2022) - Carter, Gregory; Sperandei, Sandro; Spittal, Matthew J.; Chitty, Kate; Clapperton, Angela; Page, Andrew
Abstract: Introduction: More than half of suicide decedents have no contact with mental health services 12 months before death. It is uncertain if they have different characteristics than decedents who use mental health services. Methods: A case‐series design. Participants 45 years and older, who died by suicide (2006–2018). Comparisons were made between those who did and did not have contact with mental health services, using individually linked data from federal services in the Medicare Benefits Schedule (MBS) and Pharmaceutical Benefits Scheme (PBS). Results: Of 186 cases, 71% had no contact with mental health services. Physical health services were used equally by 75%. Psychiatric medication use was uncommon, except for antidepressants, 50% with mental health service contact and 20% with no contact. Older age, lower income, involuntarily unemployed, firearms as suicide method, greater physical disability, less functional impairment due to emotional problems and lesser proportions with mental illness, were associated with no contact with mental health services. Conclusions: For suicide prevention, middle‐older aged adults may have less requirement for mental health intervention, and greater requirement for the development of complementary interventions focused on physical health and social issues, which are not necessarily best delivered by clinical mental health services.